Arterielle Hypertonie bei Kindern und Jugendlichen - Bald, Martin; Wühl, Elke (Monatsschrift Kinderheilkunde, 2019)
The prevalence of arterial hypertension in childhood and adolescence has significantly increased during recent years, among others due to an increase in the prevalence of overweight and obesity. For this reason, regular blood pressure control measurements are recommended from the age of 3 years. If findings are ambiguous or office blood pressure values are constantly elevated, 24‑h outpatient blood pressure monitoring is recommended. Further diagnostics are necessary to exclude secondary hypertension, to determine end-organ damage and the assessment of additional cardiovascular risk factors. Even with high normal blood pressure values, life style modifications including avoidance of overweight, with a healthy diet and daily physical activity are recommended. Antihypertensive treatment is indicated for severe hypertension or populations at risk. The choice of medication should be based on concomitant diseases and risk factors as well as the side effect profile. The aim is a long-lasting normalization of blood pressure in order to prevent cardiovascular diseases in the long term.
Gesehen am 19.06.2019